A resource‐based view of green innovation as a strategic firm resource: Present status and future directions - Khanra, Sayantan; Kaur, Puneet; Joseph, Rojers P; Malik, Ashish; Dhir, Amandeep (Business strategy and the environment, 2022)
Green innovation could become a valuable firm resource for establishing competitive advantage while simultaneously contributing towards sustainable development; in other words, green innovation has the potential to address the dilemma between consuming available resources and preserving them for the future. However, there is a dearth of studies systematically examining the present structure and future scope of research on green innovation as a firm resource. Seeking to explain the sustainable development dilemma of green innovations through the theoretical perspective of the resource‐based view of the firm, we address this gap with a comprehensive bibliometric analysis of 951 relevant articles. The key contributors to the extant literature are recognised with bibliographic coupling, citation analysis and co‐authorship analysis. A co‐citation analysis identifies four major thematic areas of research: green supply chain management, green product design, corporate environmental responsibilities and social sustainability. Further, a dynamic co‐citation analysis tracks the progression of these thematic areas. Content analysis of the thematic areas provides insights into the status of the research domain. This study also contributes to the extant literature by identifying prestigious articles on green innovation as a firm resource, analysing the co‐occurrence of keywords and suggesting future research agendas.